Managing an economy under EMU : the case of Ireland - Gerald, John Fitz (2001)
Provides a brief description of Ireland's experience of three different monetary regimes. Describes the economic reasoning behind Ireland's decision to join the Economic and Monetary Union (EMU). Discusses Ireland's experience of the first two and a half years of EMU. Focuses on the implications of this experience for economic policy in Ireland, and in other regional economies within the EMU.